Dividend Policy in Malaysia: A Comparison of Determinants Pre and Post Malaysian Code on Corporate Governance - Mohd Ashari Bakri; Mohamad Isa Abd Jalil; Zakiah Hassan (Perpustakaan UUM, 2021)
This study was aimed at examining the differences between dividend policy determinants pre- and post-Malaysian Code on Corporate Governance (MCCG) 2012. Several factors, including profitability, lagged dividend, free cash flow, debt, firm size, investment opportunities and market risk were tested. The study investigated a total number of 631 non-financial firms in Malaysia that covered 7830 firm-year observations from 2005 to 2011 (pre-MCCG) and from 2013 to 2019 (post-MCCG). The study used pooled Ordinary Least Square (OLS) and random and fixed effect, with a robust standard error. The results demonstrated that from seven factors tested only four factors were found to be significant in determining dividend policy in pre-MCCG, and five factors in post MCCG. The pre-MCCG test revealed that before the revised MCCG 2012, the factors determining dividend policy were as follows: profitability, lagged dividend, debt, and firm size. However, there were slight changes in the range of determinants affecting dividend policy, Post-MCCG 2012. The post MCCG test revealed that profitability, lagged of dividend, and firm size consistently determined firm dividend policy; however, debt was no longer a significant determinant of dividend policy post MCCG. Additionally, investment opportunity and market risk were found to be significant determinants of dividend policy post-MCCG in 2012.